Optimizing Botox regimens in patients with adductor spasmodic dysphonia and essential tremor of voice: A 31‐year experience. Issue 5 (19th September 2022) - Stone, Amy; Powell, Maria E.; Hamers, Kaitlyn; Fletcher, K. Charles; Francis, David O.; Courey, Mark S.; Netterville, James L.; Garrett, C. Gaelyn
Abstract: Objective: The purpose of this study was to quantitatively compare the effectiveness of unilateral and bilateral botulinum toxin A (BTX‐A) injections for mitigating undesirable weak/breathy voice quality and dysphagia for patients with adductor spasmodic dysphonia and/or essential tremor of voice (ETV). Methods: Data were collected from the medical records of 319 patients, yielding three treatment cohorts: patients who received an equal dose bilateral injection regimen (BL=) throughout their course of treatment at VUMC, patients who switched to a unilateral injection regimen (UL), and patients who switched to an unequal dose bilateral injection regimen (BL≠). Changes in length of improvement, duration of weak/breathy voice, and dysphagia severity were compared. Results: The BL = treatment group reported the longest duration of improved voice. Shorter periods of improved voice were reported at baseline by patients who later switched to UL or BL ≠ injection regimens. Patients receiving UL injections reported significantly reduced weak/breathy voice and dysphagia. Patients receiving BL ≠ injections reported increased length of improved voice; however, dysphagia symptoms increased. Ninety‐two percent of patients with ETV switched to a UL regimen, with 61% of patients transitioning within the first three injections. Conclusions: Patients with pronounced dysphagia and extended periods of weak/breathy voice may benefit from a UL injection approach to mitigate side effects from BTX‐A without sacrificing improved voice outcomes. For patients seeking to extend their length of improved voice, a BL ≠ injection regimen may be effective provided the adverse side effects from BTX‐A are minimal. Patients with ETV may benefit from a UL injection approach at the outset of their course of treatment with BTX‐A. Level of evidence: III.